Go gently : actionable steps to nurture yourself and the planet - Wright, Bonnie, 1991- (Mariner Books, 2022)
"An inspiring and approachable tip-filled guide to changing your habits, living more sustainably, and taking action, by Greenpeace ambassador Bonnie Wright (Ginny Weasley in the Harry Potter movies). Go Gently is a guide for sustainability at home that offers simple, tangible steps toward reducing our environmental impact by looking at what we consume and the waste we create, as well as how to take action for environmental change. The title reflects Bonnie Wright's belief that the best way to change our planet and ourselves is through a gentle approach, rather than a judgmental one. This is a book of do's rather than don'ts. It's also an invitation to Wright's followers to join her on this journey to sustainability. Going through every room in her home, Wright helps us assess which products are sustainable, and alternatives for those that are not. She shares recipes to avoid waste, homemade self-care products to avoid packaging, small space-friendly gardening ideas, and a template for creating your own compost system. Finally, to sustain yourself, there are exercises and meditation prompts to keep you energized, plus info on how to get involved in community and organizations."--Amazon.com.